Physiological and biochemical adaptive responses and defense mechanisms to withstand increasing ultraviolet radiation and temperatures in an Antarctic meiofauna organism - I. Giovannini; R. Guidetti; T. Altiero; M. Cesari; R. Bertolani; L. Rebecchi; G. Montorfano; A.M. Rizzo (2013)
Climate changes, are leading to an increase in ultraviolet radiation (UV), by reducing the amount of tropospheric ozone. All life forms are susceptible to UV and their effects are reinforced by rising temperatures, which lead to consequences on human and ecosystems health. This has become an important and emerging issue, particularly for the Polar regions. Antarctic micrometazoans are especially vulnerable to the synergistic effects of these two environmental factors, as their growing season happens in the spring period of ozone depletion. Tardigrades, together with rotifers, represent the main terrestrial invertebrate components of Antarctic fauna in terms of distribution, number of specimens, and colonized substrates. They survive adverse environmental conditions (i.e. dehydration or freezing) by temporally suspending their metabolism. This adaptive strategy, called cryptobiosis, allows to maintain cell integrity and to repair damaged proteins, lipids, and nucleic acids (Guidetti et al. 2011, J. Insect Physiol. 57:567–576). During cryptobiosis, harmful reactive oxygen species(ROS) are found to be one important source of cell damage. Tardigrades developed natural countermeasures to cope with the oxidative stress, showing a highly efficient antioxidant system (Rizzo et al. 2010, Comp. Biochem. Physiol. B 156:115-121). In addition, recent studies indicate that the ability to repair DNA damage may be central in tolerating desiccation and also harmful UV (Gladyshev & Meselson 2008, PNAS 105:5139–5144). For these reasons, tardigrades are good animal models to study the combined effects of UV and temperature changing on Antarctic organisms, and to detect molecules acting as bio-protectants for future bio-prospecting studies. We analyzed the physiological and biochemical responses of Acutuncus antarcticus, one of the most abundant tardigrade species colonizing bryophytes and freshwater sediments of Antarctica. Animals were exposed to increasing UV and temperatures,in order to evaluate the separate and synergistic ...